Sustained improvements in pain, mood, function and opioid use post interdisciplinary pain rehabilitation in patients weaned from high and low dose chronic opioid therapy. Issue 7 (July 2017) - Huffman, Kelly L.; Rush, Taylor E.; Fan, Youran; Sweis, Giries W.; Vij, Brinder; Covington, Edward C.; Scheman, Judith; Mathews, Manu
Abstract : Abstract: Increased prescribing of opioids for chronic noncancer pain is associated with significant social costs, including overdose and addiction. In this context, there is interest in interdisciplinary chronic pain rehabilitation programs focusing on self-management and minimizing opioid use. This study examined outcomes of patients weaned from opioids in an ICPRP from 2007 to 2012. Participants included 413 patients on high dose chronic opioid therapy (COT; >100 mg), 528 on low dose COT, and 516 not on opioids (NO). Outcomes were assessed at discharge, 6, and 12 months posttreatment through self-report and chart review. One thousand one hundred ninety-four participants completed treatment (81.95%); 86.74% of those on opioids were weaned. High doses were less likely to complete (78.45%) than NO participants (85.27%; P < 0.05). Results showed immediate ( P < 0.01) and sustained improvements ( P < 0.05) in pain severity, depression, anxiety, and functional impairment with no group differences. Effect sizes ranged from medium to large (Cohen d values 0.57-1.96). Longitudinal medication use data were available for 319 no dose and 417 weaned participants; opioid resumption rates were 10.51% and 30.70% respectively. There were no differences in resumption between the high dose and low dose groups. Logistic regression analyses determined that opioid dose predicted neither treatment completion nor opioid resumption. Anxiety predicted completion, and functional impairment predicted opioid resumption within 1 year of discharge. Results suggest that patients on COT can be successfully weaned with long-term benefits in pain, mood, and function. Targeting anxiety and functional restoration may increase success rates. Abstract : Patients weaned from opioids (n = 1194) within a pain rehabilitation program showed benefits in pain, mood, and function 1 year later and ∼70% remained opioid free.